Perlindungan Hukum terhadap Pasien BPJS yang Mengalami Cacat Fisik Akibat Malpraktek Dokter - I Wayan Agus Paramartha; I Nyoman Putu Budiartha; I Putu Gede Seputra (Warmadewa Press, 2021)
The need to fulfill patient rights stemming from the obligations of a doctor in a hospital so that it is deemed necessary to regulate medical practice in a law. Based on this background, it can be formulated that the purpose of this study is to determine the responsibility of doctors for malpractice that results in physical disabilities in patients and to determine legal protection for BPJS patients who experience physical disabilities due to malpractice of doctors. The type of research in this paper uses normative legal research. The method that the author uses in collecting legal assistance is the method of observation and recording of a literature review obtained to be collected and arranged in such a way. The conclusion of this study is that if a doctor is responsible for carrying out medical treatment, it has been proven and can be proven that he has committed malpractice, then the forms of punishment that can be given are the release of permission from the medical profession by the Indonesian Medical Discipline Honorary Council. However, when there is a report from the victim or patient who is harmed to the police and it has been proven or can be proven, the doctor can be subject to civil, criminal and administrative penalties. Legal protection for BPJS patients who experience physical disabilities due to malpractice of doctors has been regulated in positive law in force in Indonesia